2014
DOI: 10.3389/fpsyt.2014.00171
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity and Motoric Activity in ADHD: Characterization, Assessment, and Intervention

Abstract: The aim of the present literature review is threefold. (1) We will review theories, models, and studies on symptomatic hyperactivity and motoric activity in attention-deficit/hyperactivity disorder (ADHD). (2) Another focus will be on assessment methods that have been proven to be effective in the detection of hyperactivity and motoric activity in children, adolescents, and adults with and without ADHD and emerging areas of research in the field of ADHD. We will compare subjective methods (i.e., rating scales)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 126 publications
(118 reference statements)
0
22
0
1
Order By: Relevance
“…timing, inhibiting responses, tolerating delay) give rise to the highly diverse symptom expression that characterizes ADHD. 13,33 Delayed development within the later maturing areas of the brain has been suggested as a causal mechanism in some theories. 13,34 STRUCTURAL NEUROIMAGING Several recent reviews have detailed structural imaging in children with ADHD.…”
Section: Neurobiologymentioning
confidence: 98%
See 3 more Smart Citations
“…timing, inhibiting responses, tolerating delay) give rise to the highly diverse symptom expression that characterizes ADHD. 13,33 Delayed development within the later maturing areas of the brain has been suggested as a causal mechanism in some theories. 13,34 STRUCTURAL NEUROIMAGING Several recent reviews have detailed structural imaging in children with ADHD.…”
Section: Neurobiologymentioning
confidence: 98%
“…32,34 State (vigilance) regulation theories hypothesize that the core deficit in ADHD is impaired regulation of activation state (arousal). 33,36 Some symptoms are attributed to dysfunctional fluctuations in arousal (e.g. deficits in sustained attention) whereas others are a result of autoregulatory efforts to reach stability by increasing external stimulation (e.g.…”
Section: Neurobiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies using actigraphy reported on gross motor activity in the course of schizophrenia ( 16 , 17 ). Finally, Gawrilow and colleagues summarized the importance of motor activity in ADHD ( 18 ).…”
mentioning
confidence: 99%